(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In modern military education, ensuring psychological stability among cadets during tactical exercises is critical for effective performance and resilience in real combat situations. This article explores key mechanisms and strategies aimed at maintaining and strengthening cadets’ psychological stability under stressful training conditions. The study highlights the role of psychological training, stress management techniques, leadership support, and the implementation of coping strategies tailored to military contexts. Through a review of both Uzbek and international practices, the article provides a comprehensive overview of effective approaches to enhance mental resilience in cadets, contributing to their overall combat readiness.